Analysis of Paragliding Sports Tourism in Pasir Gowong, Tasikmalaya, West Java, Indonesia - Riswan Firmansyah; Rizal Ahmad Fauzi; Adang Sudrazat (Journal of Physical Education Health and Sport, 2026)
The research focuses on analysis destination readiness and identifying key factors that influence sustainable, community-based, and risk-aware sport tourism development. This study aims to analyze the potential and challenges of paragliding sport tourism development in Pasir Gowong, Tasikmalaya, using the Marketability, Sustainability, Participatory, and Disaster Mitigation (MSP+DM) framework. This study employs a descriptive qualitative approach. Data were collected through in-depth interviews with key informants, field observations, and document analysis. The informants consisted of tourism managers, local government representatives, sport organizations, and paragliding practitioners. Data validity was ensured through triangulation techniques by systematically comparing findings from interviews, observations, and documentation within the MSP+DM analytical framework. The findings indicate that Pasir Gowong has strong marketability potential, supported by unique and repeatable flying experiences, attractive natural landscapes, and the availability of basic facilities. From a sustainability perspective, the destination demonstrates initial efforts to preserve environmental conditions and align tourism activities with local socio-economic dynamics, although structured management systems and long-term planning remain limited. In the participatory aspect, stakeholder involvement is evident through community participation in services, land provision, and event activities, yet it is still uneven and not fully institutionalized. Meanwhile, disaster mitigation practices are implemented operationally through weather monitoring, instructor supervision, and safety considerations; however, the absence of formal standard operating procedures, emergency response plans, and inter-agency coordination remains a significant limitation. In conclusion, Pasir Gowong shows promising potential as a sport tourism destination, but requires improvements in accessibility, governance, community empowerment, and systematic risk management to achieve sustainable and competitive development.